Synthesis and Characterization of ZrO2:ZnO Nanoparticles Prepared by Laser Induced Plasma - A. Mohammed, Marwa; Hashim, Hassan Nasir (Al-Nahrain Journal of Science, 2024)
In this research, we looked at how laser energy affected the structural and optical characteristics of ZrO2:ZnO thin films at mixing ratios (0.1, 0.2, 0.3 and 0.4) that were applied on glass slides using the pulse laser deposition technique (PLD). Nd:YAG laser was utilized with a wavelength of 1064 nm, a pulse width of 9 ns, and an energy of 320 mJ. The X-ray diffraction patterns revealed that all the films had a polycrystalline hexagonal crystal structure. AFM was used to measure the topography of the film's surface, and the results revealed that the average roughness and grain size increased. After analyzing the optical characteristics of each film, it was discovered that the absorption coefficient in the 200–1000 nm wavelength range increases at 320 mJ of laser energy and that the optical energy gap value for indirect permitted transitions decreases between 3.58 and 3.4 eV.